Why not vaginal?—Nationwide trends and surgical outcomes in low‐risk hysterectomies: A retrospective cohort study - Johanna Wagenius; Sophia Ehrström; Karin Källén; Jan Baekelandt; Andrea Stuart (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction The rate of vaginal hysterectomies is declining globally. We investigated surgical techniques, outcomes, and costs in a large national cohort of benign hysterectomies with prerequisites for vaginal surgery. Material and Methods A retrospective register‐based cohort study with benign hysterectomies in the Swedish GynOp registry 2014–2023 (n = 17 804). Inclusion criteria were non‐prolapse, non‐endometriosis with uterus weight <300 g. The cohort was divided into a low‐risk and a standard group, with the low‐risk group having optimal conditions for vaginal hysterectomy: no previous caesarian section (CS), no previous abdominal surgery, Body Mass Index (BMI) <30, and no nulliparous patients. Surgical outcomes were quantified using crude and adjusted risk ratios (RR, ARR). Costs were calculated and compared between abdominal (AH), laparoscopic (LH), robot‐assisted (RH), and vaginal hysterectomies (VH). Results The rate of AH and VH decreased during the period studied. RH increased and was the most common surgical technique 2021–2023 (33.2%). VH had the shortest surgical time and was the cheapest method. In the low‐risk group, 25.2% of the patients were operated on vaginally. AH had more postoperative complications and longer hospitalization compared to VH in the low‐risk group. LH had less severe intraoperative complications, ARR = 0.38 (95% CI 0.17–0.86) but more mild postoperative complications, ARR = 1.24 (95% CI 1.05–1.46) compared to VH in the low‐risk group. LH had more conversions, ARR = 1.46 (95% CI 1.00–2.12), longer surgical time, ARR = 2.73 (95% CI 2.46–3.00) and longer hospital stay, ARR = 1.26 (95% CI 1.12–1.43) compared to VH. Mild (ARR = 0.33, 95% CI 0.16–0.66) and severe (ARR = 0.17, 95% CI 0.05–0.58) intraoperative complications and bleeding >500 mL (ARR = 0.12, 95% CI 0.04–0.34) were less common in RH versus VH in the low‐risk group. There were no differences between RH and VH regarding postoperative complications and reoperations. Surgical time <45 min was less common in RH versus VH (ARR = 0.47, 95% CI 0.42–0.54) and RH had a significantly longer postoperative hospital stay (ARR = 1.16, 95% CI 1.02–1.33). Conclusions A decline of vaginal hysterectomies in Sweden 2014–2023 among patients with prerequisites for vaginal surgery was shown. VH was the cheapest method with few postoperative complications and short hospitalization. Our results support the vaginal route in low‐risk hysterectomies.